The role of caregivers in the clinical pathway of patients newly diagnosed with breast and prostate cancer: A study protocol - Cincidda, Clizia; Oliveri, Serena; Sanchini, Virginia; Pravettoni, Gabriella (Frontiers in Psychology, 2022)
Background. Caregivers may play a fundamental role in the clinical pathway of cancer patients. They provide emotional, informational, and functional support as well as practical assistance, and they might help mediate the interaction and communication with the oncologists when care options are discussed, or decisions are made. Little is known about the impact of dyadic dynamics on patient-doctor communication, patient’s satisfaction, or adherence to the therapies. This study protocol aims to evaluate the efficacy of a psychological support intervention on patients-caregivers relationship and their alignment in the treatment decision-making (TDM) process and estimate related improvement in patient’ compliance/adherence to treatments. Methods. A total of 102 patients-caregivers’ dyads will be involved, among breast and prostate cancer patients. The study entails a pre- post- evaluation through psychological questionnaires, with a randomization of participants in two conditions, the experimental one in which subjects participate in a psychological support consultation, and the control one, where dyads do not receive any intervention. A follow up after 6 months from the enrollment is planned. Discussion. A positive impact of the psychological support intervention on patients’ anxiety, depression, distress, and perceived social support is expected. Such improvements can directly affect patients’ satisfaction and adherence to treatments. Data gathered from this study may inform health care providers, policy makers, and public health managers about the importance of caregiver’s involvement in the cancer care pathway, and the best way to manage it. A further impact is to develop a specific intervention protocol to support caregivers’ involvement in cancer care pathway, improve patient’s wellbeing, the interaction with physicians and the compliance with the cancer treatment.